Urgensi Hak Buruh dalam Kebijakan Pengupahan - Quri’syaich Say Mandari; Ernu Widodo; Fathul Hamdani (Lembaga Pengembangan Kinerja Dosen, 2025)
Every worker as an Indonesian citizen has the desire to get a decent and prosperous life and get a decent job. A prosperous life can be achieved through the implementation of obligations as workers, the mandate is contained in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia which states: